ETIKA MENUNTUT ILMU DALAM QS. AL-KAHFI AYAT 60-82 REINTERPRETASI KISAH NABI MUSA DALAM UPAYAMENGHADAPI DEKADENSI MORAL PELAJAR - Mutaqin Al- Zamzami (Islamic University of Indonesia, 2018)
For moslems, al-Qur’an is a guide book for everything and its’ content will always be relevant over times. Therefore, it is necessary to refer problems in educations to al-Qur’an with its interpretations, both classic and new interpretation. One of many problems in education is students’ ethics in the process of education. So far, moral decadence is a main concern that yet to be solved. There are many violence against teachers that show us that morality issue is a major consideration in education. Based on this background, the writer observe that it is important to formulate an ethical basis that are inspired by islamic primary sources, al- Qur’an and al-Sunnah.One of Quranic content that is relevant with this matter is Moses PBUH story in surah al- Kahfi verses 60-82, as one of the goals of al-Qashash (Quranic stories) is as lesson from the previous ummah. In addition, the verses clearly show the ethics of the Prophet Moses when studying with the Prophet Khidr, such as: being polite, accepting punishment, obedience etc. This work will use thematic analytical methods and see the verse general discussion of the Prophet Moses, in order to bring up new meanings of ethical values in these verses. Keywords : Ethics, Qashash (Quranic Stories), Education, Khidir, Moses.